DESAIN OTOMATISASI TEKNOLOGI FILTRASI DINAMIS PADA SISTEM RESIRKULASI AIR LAUT UNTUK PEMELIHARAAN DAN BUDIDAYA KARANG - Salasi Wasis Widyanto; Ma’muri Ma’muri; Ari Kuncoro; Susilo Wisnugroho; Nanda Radhitia Prasetiawan (Universitas Mataram, 2021)
Damage to coral reefs that have a bad impact on marine ecosystems requires serious recovery efforts considering that coral growth can take a very long time. One of the efforts that can be done can be the maintenance and cultivation of coral reefs. Besides being useful for conservation purposes, this effort also has a profit-based orientation. In order to be widely used so that it can be implemented on various lands, this maintenance and cultivation effort requires technology that supports the minimum frequency of manual water changes through a seawater recirculation system by maximizing the best filtration system integrated with overall system automation. The design of the formulation is the goal of this activity. The activity method refers to the technical guidelines for engineering the Agency for the Assessment and Application of Technology (BPPT) which includes conceptual design, exploration, observation, measurement, calculation, preliminary design, and detailed design. The results achieved are in the form of an automated design of dynamic filtration technology on a seawater recirculation system for coral maintenance and cultivation, which consists of a Recirculation Aquaculture System (RAS) using dynamic filters in the form of biological and chemical filters to optimize the biogeochemical cycle of nitrogen with organic carbon and CO2 supply. Automatic monitoring and control is carried out by a micro controller that controls other mechanical and electronic devices. The conclusion that can be drawn is that the automatic design of dynamic filtration technology on a seawater recirculation system for coral maintenance and cultivation has been successfully made using a skimerless and automated system.